2001
DOI: 10.1024//1421-0185.60.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of marital distress by enhancing the coping skills of couples: 1-year follow-up-study

Abstract: This article presents a new preventive approach (Couples Coping Enhancement Training: CCET) aimed at expanding upon the scope of current prevention programs by focussing on stress issues and individual and dyadic coping skills. The cognitive behavioral prevention program is based on stress and coping research in couples and seeks to improve important skills with an 18-hour course. The effectiveness of the approach is examined with respect to 143 couples over a period of one year. The results show that couples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 16 publications
5
79
1
Order By: Relevance
“…There is an existing couple intervention protocol that specifically targets dyadic coping, Couples Coping Enhancement Training (CCET; Bodenmann & Shantinath, 2004). Outcome studies of CCET demonstrate marked gains in marital quality evident after one year follow-up (Bodenmann, Charvoz, Cina, & Widmer, 2001) and improved dyadic coping that persist two years later (Bodenmann, Perrez, Cina, & Widmer, 2002). Research shedding light on potential mechanisms of change in the couple relationship that might impact diabetes outcomes is important, as the only randomized control trial to date that has tested a couple intervention for weight-loss in patients with type 2 diabetes was largely ineffective (Wing, Marcus, Epstein, & Jawad, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…There is an existing couple intervention protocol that specifically targets dyadic coping, Couples Coping Enhancement Training (CCET; Bodenmann & Shantinath, 2004). Outcome studies of CCET demonstrate marked gains in marital quality evident after one year follow-up (Bodenmann, Charvoz, Cina, & Widmer, 2001) and improved dyadic coping that persist two years later (Bodenmann, Perrez, Cina, & Widmer, 2002). Research shedding light on potential mechanisms of change in the couple relationship that might impact diabetes outcomes is important, as the only randomized control trial to date that has tested a couple intervention for weight-loss in patients with type 2 diabetes was largely ineffective (Wing, Marcus, Epstein, & Jawad, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It is even more important to do so since it is known that coping skills have been linked to marital adjustment in both non-distressed and distressed couples [110][111][112], as well as in couples facing specific stressors [113,114]. Indeed, Bodenmann et al [115] included the enhancement of coping abilities (at individual and dyadic levels) as a specific target in their preventive training programme for couples (Couples Coping Enhancement Training (CCET)), itself inspired by the work of Markman's team [116]. Examining the efficacy of this programme over a period of 1 year among 143 couples from the general population, these authors demonstrated that couples participating in the programme significantly improved in their marital quality following the training and that this effect remained stable for 1 year.…”
Section: Coping and Marital Adjustmentmentioning
confidence: 98%
“…Results of these further studies aiming to identify critical variables associated with the adjustment process of individuals with TBI and their spouses could then inform the adaptation of sound intervention programmes destined to TBI couples. A training programme, like that of Bodenmann et al [115], could represent a promising starting point to tackle this issue.…”
Section: Future Directionsmentioning
confidence: 99%
“…Bodenmann, (1997Bodenmann, ( , 2000Bodenmann, ( , 2005 describes dyadic coping as a process, which is characterized by specific stress signals of one partner and verbal or nonverbal responses to these signals by the other. He distinguishes several forms of dyadic coping processes: common dyadic coping (both partners engage symmetrically in the coping process), supportive dyadic coping (one partner supports the other in stressful situations) or delegated dyadic coping (one partner asks the other partner to take over some of his tasks; Bodenmann, Charvoz, Cina, & Widmer, 2001). Supportive dyadic coping either focuses on the problem (e.g., giving advice) or on emotions (e.g., providing tender gestures).…”
mentioning
confidence: 99%